2015
DOI: 10.1542/peds.2015-0017
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Risk Factors and Outcomes in Gastroschisis: A Meta-Analysis

Abstract: BACKGROUND AND OBJECTIVE: Gastroschisis is a congenital anomaly with increasing incidence, easy prenatal diagnosis and extremely variable postnatal outcomes. Our objective was to systematically review the evidence regarding the association between prenatal ultrasound signs (intraabdominal bowel dilatation [IABD], extraabdominal bowel dilatation, gastric dilatation [GD], bowel wall thickness, polyhydramnios, and small for gestational age) and perinatal outcomes in gastroschisis (bowel atresia, intra uterine dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
60
0
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 50 publications
5
60
0
13
Order By: Relevance
“…Polyhydramnios was predictive of CG, which is in agreement with data from a recent meta-analysis [14] . This marker may be present as a consequence of bowel damage, which impairs fetal swallowing.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Polyhydramnios was predictive of CG, which is in agreement with data from a recent meta-analysis [14] . This marker may be present as a consequence of bowel damage, which impairs fetal swallowing.…”
Section: Discussionsupporting
confidence: 90%
“…However, few studies have investigated the associations between US markers and CG [8,12] . Of these studies, intra-abdominal bowel dilatation (IABD) was theAccording to a recent meta-analysis of publications on US markers used to predict fetal gastroschisis prognosis [14] , limitations remain because the majority of the studies included small sample sizes, utilized different thresholds to define the US markers as abnormal, assessed limited outcome measures, and investigated the US markers at limited gestational ages (GAs). Therefore, considering the relevance of CG in association with fetal gastroschisis outcomes, we aimed to obtain additional, good-quality, robust data, including several US markers, from a single center to provide additional information regarding the usefulness of US markers in the prediction of CG.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, IABD at 30 weeks’ gestation only occurred in simple gastroschisis, which suggests that IABD is not a clear sign of complex gastroschisis. A recent meta-analysis in contrast showed a significant association between IABD and bowel atresia, although the positive predictive value was low (22%, derived from table 4 of that paper) and thresholds of bowel dilatation differed between studies 7. Furthermore, EABD –with thresholds ranging from 6 to 30 mm—did not predict bowel atresia 7.…”
Section: Discussionmentioning
confidence: 92%
“…A recent meta-analysis in contrast showed a significant association between IABD and bowel atresia, although the positive predictive value was low (22%, derived from table 4 of that paper) and thresholds of bowel dilatation differed between studies 7. Furthermore, EABD –with thresholds ranging from 6 to 30 mm—did not predict bowel atresia 7. One recent study showed an association between GA-corrected EABD and complex gastroschisis 24.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation